Improving Digital Service and Marketing Capabilities for MSMEs: Community Service at Brangkal Printing - Yusriyah Rahmah (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, yet many still face challenges in adopting digital technology, particularly in services and marketing. Brangkal Printing, one of the MSMEs in Pandanlandung Village, demonstrated limitations in its customer service system and digital marketing strategy, impacting market reach and service efficiency. This community service activity aimed to improve Brangkal Printing's digital capacity through training in digital ordering systems, Google Drive-based catalog management, and strengthening social media marketing based on the principles of The Seven Laws of Digital Marketing. Implementation methods included problem identification, technical training, customer education, Focus Group Discussions (FGDs), and impact evaluation. The results of the activity showed a significant improvement in the owner's and staff's ability to manage digital services, as well as an increase in the number of orders through online platforms. The digital catalog system also helps consumers select products without having to visit the business location in person. The main recommendation from this activity is the need for continued mentoring and consistency in implementing digital strategies so that MSMEs can transform sustainably in the digital economy era.